About Decon'21 - Kadriye Funda Akaltan (Ankara University, 2021)
Decon'21, the first international dental education congress in Turkey, was held online from January 11 to 15, 2021, with the theme of dental emergency action plans in pandemic conditions, "what we can do about undergraduate dental education, and recommen- dations for Covid-19."